The making of Japanese settler colonialism : Malthusianism and trans-Pacific migration, 1868-1961 - Lu, Sidney Xu, 1981- (Studies of the Weatherhead East Asian Institute, Columbia University., 2019)
This innovative study demonstrates how Japanese empire-builders invented and appropriated the discourse of overpopulation to justify Japanese settler colonialism across the Pacific. Lu defines this overpopulation discourse as 'Malthusian expansionism'. This was a set of ideas that demanded additional land abroad to accommodate the supposed surplus people in domestic society on the one hand and emphasized the necessity of national population growth on the other. Lu delineates ideological ties, human connections and institutional continuities between Japanese colonial migration in Asia and Japanese migration to Hawaii and North and South America from 1868 to 1961. He further places Malthusian expansionism at the center of the logic of modern settler colonialism, challenging the conceptual division between migration and settler colonialism in global history. This title is also available as Open Access.